The expression of intracellular cytokines of decidual natural killer cells in unexplained recurrent pregnancy loss. (18th August 2022) - Liu, Jia; Dong, Peng; Jia, Ningyi; Wen, Xi; Luo, Lanrong; Wang, Shijun; Li, Jian
Abstract: Objective: This study aims to investigate the expression levels of TNF-α, IFN-γ, IL-4, and IL-10 in dNK cells and determine whether or not the MAPK signal pathway is involved in the regulation of cytokine secretion by dNK cells at the maternal–fetal interface. Methods: In this study, we collected decidua specimens from patients with apparently normal pregnant and unexplained recurrent pregnancy loss (URPL) and extracted dNK cells by enzymatic digestion. Then the expression of cytokines were analyzed by flow cytometry and Real-Time PCR respectively. Results: The secretions of both IFN-γ and TNF-α in dNK cells in URPL were significantly higher than those in normal pregnancy. Furthermore, p38/MAPK inhibitors can inhibit the secretion of four cytokines in normal pregnancy, while in URPL cases, p38/MAPK inhibitors only significantly inhibit the secretion of IL-4 and IFN-γ. ERK inhibitors had no effect on the expression of all four cytokines and JNK/MAPK inhibitors varied on different cytokines. Conclusion: URPL is associated with a NK1 cytokine profile. MAPK signaling pathway is involved in the regulation of cytokine secretion by decidual NK cells at maternal–fetal interface.